The Application of ChatGPT in Problem-Based Learning Management on the Topic of Work and Energy - Ratniyom, Jadsada; Srisamarng, Atchara (Journal of Technical and Engineering Education, 2025)
In an era where technology and artificial intelligence (AI) are playing an increasingly significant role in global education, the integration of AI, particularly ChatGPT, into science learning management in Thailand is still limited. ChatGPT is an AI system that can simulate conversations with users, generating a variety of responses by inputting questions into a chat interface. Due to ChatGPT's capabilities, we were interested in applying ChatGPT to problem-based learning management to investigate the efficiency (E1/E2) of this learning approach against the specified criteria of 80/80. Additionally, the study aimed to compare the learning achievement in science before and after the implementation of ChatGPT integrated with problem-based learning management. The sample group consisted of grade 8 students from a school in Bangkok. The research tools included lesson plans based on problem-based learning management with ChatGPT and an achievement test in science. Statistical data was analyzed using the mean, standard deviation, and t-test for dependent samples. The research findings indicated that: 1) the efficiency (E1/E2) of integrating ChatGPT into problem-based learning management was 87.50/89.67, meeting the specified criteria of 80/80, and 2) students who participated in problem-based learning management integrated with ChatGPT showed a statistically significant improvement in learning achievement after the implementation of this learning approach, with significance at the 0.01 level. The findings of this research suggested that integrating AI technology into learning management can serve as an effective approach to enhance learning efficiency and improve learning achievement in science.